Targeting newly identified ERβ/TGF‐β1/SMAD3 signals with the FDA‐approved anti‐estrogen Faslodex or an ERβ selective antagonist in renal cell carcinoma. Issue 12 (30th October 2018) - Song, Wenbin; He, Dalin; Chen, Yule; Yeh, Chiuan‐Ren; Hsu, Iawen; Huang, Qingbo; Zhang, Xu; Chang, Luke Sien‐Shih; Zuo, Li; Chen, Jiasheng; Doersch, Karen M.; Chang, Chawnshang; et al.
Abstract : Renal cell carcinoma (RCC) has the third highest mortality rate among urological tumors, and 20–30% of RCC patients present with metastatic RCC at the time of diagnosis. Although recent studies have indicated that estrogen receptor β (ERβ) could play promoting roles in RCC progression, the detailed mechanisms remain to be clarified. In the present study, we found that expression of ERβ, but not ERα, increases with tumor stage and grade, and also observed that modification of ERβ signals using estrogens/anti‐estrogens, shRNA knockdown of ERβ and overexpression of ERβ using ectopic cDNA affects RCC cell proliferation, migration and invasion. Mechanism analysis revealed that ERβ can promote RCC cell invasion via an increase in transforming growth factor β1 (TGF‐β1)/SMAD3 signals, and interrupting TGF‐β1/SMAD3 signals with a TGFβR1 inhibitor can reverse/block ERβ‐increased RCC cell migration. Importantly, preclinical analyses using in vivo mouse models of RCC revealed that targeting of this newly identified ERβ/TGF‐β1/SMAD3 pathway with either the FDA‐approved anti‐estrogen ICI182, 780 (Faslodex) or a selective ERβ antagonist 4‐[2‐phenyl‐5, 7 bis(trifluoromethyl)pyrazolo[1, 5‐a]pyrimidin‐3‐yl]phenol can significantly reduce RCC tumor growth and invasion, which may be suitable as the basis for novel therapies to more effectively suppress metastatic RCC. Abstract : Targeting ERβ or its downstream TGF‐β1/SMAD3/EMT pathways may be applied as an alternative therapy strategy for metastatic RCC.